2017
DOI: 10.1111/cea.13030
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgE to peanut 2S albumin Ara h 7 has a discriminative ability comparable to Ara h 2 and 6

Abstract: SummaryBackground: Little is known on the clinical relevance of peanut 2S albumin Ara h 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…Taking together previous data and the data presented in this study, we hypothesize that determining specific IgE for Ara h 7.0201 can be of additional value in peanut allergy diagnosis. Ara h 7.0201 contains unique epitopes and is functionally as active as Ara h 2.0201 and Ara h 6.01 in inducing basophil degranulation.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Taking together previous data and the data presented in this study, we hypothesize that determining specific IgE for Ara h 7.0201 can be of additional value in peanut allergy diagnosis. Ara h 7.0201 contains unique epitopes and is functionally as active as Ara h 2.0201 and Ara h 6.01 in inducing basophil degranulation.…”
Section: Discussionsupporting
confidence: 69%
“…Although Ara h 7.0201 contains cross‐reactive epitopes with Ara h 2.0201 and 6.01, a previous study indicated that monosensitization against Ara h 7.0201 was observed in 2 of 15 patients . This suggests that Ara h 7.0201 indeed contains 1 or more epitopes not present on the other Ara h 7 isoforms or Ara h 2.0201 and 6.01.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…IgE‐binding to this allergen cannot be fully inhibited by Ara h 7.0101, although IgE‐binding to Ara h 7.0101 was completely inhibited by Ara h 7.0201. This data suggest the presence of unique epitopes on Ara h 7.0201 . By amino acid sequence comparisons, these unique epitopes might be located on the distinctive C‐terminus or created by amino acid substitutions within the flexible loops that are sensitive to pepsin or trypsin .…”
Section: Introductionmentioning
confidence: 86%
“…The cut‐off level was chosen to guarantee the detection of a broad epitope spectrum. In the next phase, the identified epitopes were validated by 25 DBPCFC‐confirmed peanut allergic (n = 22) or tolerant (n = 3) patients with sIgE levels ≥3 intensity units for Ara h 7.0201 (validation cohort) . As control, 10 sera without sIgE to Ara h 7.0201 were used.…”
Section: Methodsmentioning
confidence: 99%